A Case of Apoplexy of Rathke's Cleft Cyst Followed by Cerebral Infarction. (25th February 2015) - Ohnishi, Yu-ichiro; Fujimoto, Yasunori; Iwatsuki, Koichi; Yoshimine, Toshiki
Abstract : Rathke's cleft cyst (RCC) apoplexy is a rare clinical entity. We report a case of apoplexy of an RCC followed by cerebral infarction. A 67-year-old woman was found lying on the street unconscious. She had fallen from her motorbike. On referral to our hospital she gradually regained consciousness and presented with no neurological deficits. CT showed a round and slightly hyperdense area in the suprasellar region. However, the attending physician did not find this abnormal finding on CT and the patient was discharged the same day. Thirteen days after the first emergency visit she developed left hemiparesis and dysarthria. CT showed a round hypodense area in the suprasellar region. The change of the density in the suprasellar region on CT suggested the pituitary apoplexy. CT also showed a low density area in the territory of the right middle cerebral artery, which indicated the cerebral infarction. MR angiography revealed poor visibility and stenotic changes of right middle cerebral arteries. Transsphenoidal surgery was performed. Histopathological findings confirmed a hemorrhagic RCC. Postoperative MR angiography showed that the visibility and stenosis of right middle cerebral arteries were recovered. This is the rare case of apoplexy of an RCC followed by cerebral infarction.